FREQUENCY OF HYPONATREMIA AND IN-HOSPITAL CLINICAL OUTCOMES IN THESE PATIENTS HOSPITALIZED FOR HEART FAILURE - Ahmad, Farooq; Hadi, Abdul; Iqbal, Muhammad Asif; Khan, Ikram ullah; Adnan, Yasir; Haq, Muhammad Rehanul; Ahmad, Salman; Hafizullah, Mohammad (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the frequency of hyponatremia and in-hospital clinicaloutcomes in hyponatremic patients hospitalized for heart failure. Methodology: This was a descriptive study conducted in department ofcardiology, Lady Reading Hospital, Peshawar. Both male and female patientsaged 14 years and above admitted with heart failure fulfilling the inclusioncriteria, were included in the study. Patients were subjected to detailed historyand clinical examination. Admission Serum sodium was measured in allpatients. All the patients were managed according to guidelines. All patientswere followed for in hospital mortality and length of hospital stay (LOHS). Results: The total number of patients was 241. Mean age was 59.2 ± 14.9(range 18–100) years. Females were 123 (51%) patients. Mean serum sodiumwas 136±5.1mmol/L. Hyponatremia (serum sodium â‰¤135mmol/L) was foundin 85 (35.3%) patients. The overall in-hospital mortality rate was 5.4%. Lowervalues of serum sodium at admission was associated with higher in-hospitalmortality of 8.2% as compared with 3.8% for those patients with normal serumsodium (p=0.23). Mean Length of Hospital stay (LOHS) for overall CHFpatients was 3.8+2.24 days. Longer mean LOHS, 4.1±1.8 days was observedfor hyponatremic group compared with 3.7±2.4days for normonatremicgroup (p=0.009). Conclusions: Hyponatremia is a common finding in hospitalized heart failurepatients and is associated with significantly longer length of hospital stay. Inaddition hyponatremia is associated with higher but statistically insignificantin-hospital mortality in heart failure patients.